Avaliação da cultura de segurança do paciente em um hospital geral - Marcio Venicio Alcantara de Moraes; Rhanna Emanuela Fontenele Lima de Carvalho; Fernanda Valéria Silva Dantas Avelino (Universidade Federal de Santa Maria, 2023)
Objective: to assess patient safety culture (PSC) from the perspective of the multidisciplinary team working at a general hospital. Method: this a cross-sectional study with a quantitative approach, based on the application of the Brazilian electronic version of the Hospital Survey on Patient Safety Culture from the Agency for Healthcare Research and Quality. Data collection took place in August 2022 through E-questionário de PSC. Results: a total of 236 nursing professionals, doctors and multidisciplinary teams responded to the questionnaire. Of the 12 PSC dimensions assessed, seven stood out with percentages between 63.3% and 95%, considered strong, one with 50% positivity, indicating a growing dimension, and four with lower percentages, with 50% of positive answers identified as weak areas. Conclusion: it was possible to assess PSC in the hospital environment and perceive the strong, weak and growing dimensions. Progressing in this practice is challenging for teams looking for a reliable organization.